2018
DOI: 10.1038/s41409-017-0078-0
|View full text |Cite
|
Sign up to set email alerts
|

Selected biological issues affecting relapse after stem cell transplantation: role of T-cell impairment, NK cells and intrinsic tumor resistance

Abstract: The graft vs. leukemia (GvL) effect as a method of preventing relapse is well described after allogeneic hematopoietic cell transplantation (HCT), but the mechanisms to this effect and how tumor sometimes develops resistance to GvL are just beginning to be understood. This article reviews and expands upon data presented at the Third International Workshop on Biology, Prevention and Treatment of Relapse after Stem Cell Transplantation held in Hamburg, Germany, in November 2016. We first discuss in detail the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 107 publications
(136 reference statements)
0
7
0
Order By: Relevance
“…Of note, the general phenomena of endogenous thymic regeneration has been known for longer even than its immunological function ( Jaffe, 1924 ; Miller, 1961 ); however, the underlying mechanisms controlling this process are poorly understood ( Chidgey et al, 2007 ; Dudakov et al, 2010 ). Thus, endogenous thymic regeneration is a critical process to restore immune competence following thymic injury, although acute and profound thymic damage such as that caused by common cancer cytoreductive therapies, conditioning regimes as part of hematopoietic cell transplantation (HCT), or age-related thymic involution lead to prolonged T cell deficiency, precipitating high morbidity and mortality from opportunistic infections and may even facilitate cancer relapse ( Bosch et al, 2012 ; Clave et al, 2013 ; Dudakov et al, 2016 ; Komanduri et al, 2007 ; Legrand et al, 2007 ; Mackall, 2000 ; Mackall et al, 1995 ; Parkman and Weinberg, 1997 ; Pizzo et al, 1991 ; van den Brink et al, 2018 ; Weinberg et al, 1995 ; Williams et al, 2007 ). Recent studies have shown that thymic ILCs and ECs have profound reparative effects in the thymus after acute injury through their production of the regeneration-associated factors IL-22 and BMP4, respectively, both of which act by stimulating TECs ( Dudakov et al, 2012 , 2017 ; Wertheimer et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the general phenomena of endogenous thymic regeneration has been known for longer even than its immunological function ( Jaffe, 1924 ; Miller, 1961 ); however, the underlying mechanisms controlling this process are poorly understood ( Chidgey et al, 2007 ; Dudakov et al, 2010 ). Thus, endogenous thymic regeneration is a critical process to restore immune competence following thymic injury, although acute and profound thymic damage such as that caused by common cancer cytoreductive therapies, conditioning regimes as part of hematopoietic cell transplantation (HCT), or age-related thymic involution lead to prolonged T cell deficiency, precipitating high morbidity and mortality from opportunistic infections and may even facilitate cancer relapse ( Bosch et al, 2012 ; Clave et al, 2013 ; Dudakov et al, 2016 ; Komanduri et al, 2007 ; Legrand et al, 2007 ; Mackall, 2000 ; Mackall et al, 1995 ; Parkman and Weinberg, 1997 ; Pizzo et al, 1991 ; van den Brink et al, 2018 ; Weinberg et al, 1995 ; Williams et al, 2007 ). Recent studies have shown that thymic ILCs and ECs have profound reparative effects in the thymus after acute injury through their production of the regeneration-associated factors IL-22 and BMP4, respectively, both of which act by stimulating TECs ( Dudakov et al, 2012 , 2017 ; Wertheimer et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, endogenous thymic regeneration is a critical process to restore immune competence following thymic injury. Although there is likely continual thymic involution and regeneration in response to stress and infection in otherwise healthy people, acute and profound thymic damage such as that caused by common cancer cytoreductive therapies, conditioning regimes as part of hematopoietic cell transplantation (HCT), or age-related thymic involution, leads to prolonged T cell deficiency; precipitating high morbidity and mortality from opportunistic infections and may even facilitate cancer relapse 8,9,[57][58][59][60][61][62][63][64][65][66] . Of note, the general phenomena of endogenous thymic regeneration has been known for longer even than its immunological function 67,68 , however, the underlying mechanisms controlling this process have been largely unstudied 6,69 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the thymus is exceptionally sensitive to negative stimuli that, together with its well-characterized capacity for repair, leads to continual cycles of involution and regeneration in response to acute injury [3][4][5] . However, this capacity for regeneration declines with age as a function of thymic involution, which itself leads to a reduced capacity to respond to new pathogens, as well as poor response to vaccines and immunotherapy [6][7][8][9] . Therefore, there is a pressing clinical need for the development of therapeutic strategies that can enhance T cell reconstitution.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, other T-cell leukemia have 5-25% bone marrow contribution, which is much lower than that of T-ALL. 3,4 Irrespective of different T-ALL origins, the treatment method is coordinated with other T-cell leukemia such as T-LBL. Different modes of treatment such as radiation, stem cell transplantation, etc, in T-ALL, show better outcomes, but relapse patients' cure rates are lower than 30%, 5 and outcomes for relapsed T-LBL are even worse.…”
Section: However They Are Generally Clustered Into Two Classes Namely...mentioning
confidence: 99%